Four-Year Bacteriological Profile and Antibiotic Resistance Rate of Neonatal Blood Cultures in a Major Neonatal Intensive Care Unit (NICU) in Shiraz, Southwest Iran - Navid Omidifar; Mohammad Hadi Imanieh; Farshad Kakian; Mohsen Moghadami; Khadijehsadat Najib; Sahand Mohammadzadeh; Mohammad Motamedifar (Journal of Kerman University of Medical Sciences)
Background: Bacterial infections are the leading cause of death in newborns. The growing resistance of bacteria to antibiotics is a major concern. In this study, we identified isolates from blood cultures in the neonatal intensive care unit (NICU) of a major referral hospital in Shiraz in southwest Iran and determined antibiotic resistance patterns.Methods: All newborns admitted to the NICU were evaluated in a four-year study. The blood samples were cultured using a BACTEC system. From May 2015 to March 2020, 5937 blood culture samples were analyzed. The antibacterial sensitivity test was conducted using the disk diffusion method, following the guidelines of Clinical & Laboratory Standards Institute (CLSI) 2018.Results: In this study, 507 isolates were obtained from 5937 specimens. The most commonly isolated gram-negative bacteria were Acinetobacter (8.7%), Escherichia coli (5.7%), Klebsiella (1.6%), Enterobacter (1.4%), and Pseudomonas (0.9%). Among the gram-positive bacteria, coagulase-positive staphylococci (51.1%), coagulase-negative staphylococci (15.4%), Staphylococcus epidermidis (10.2%), non-hemolytic streptococci (2.4%), alpha-hemolytic streptococci (1.4%), and Streptococcus pneumonia (1.3%) were the most frequently isolated bacteria. Of the 318 Staphylococcus aureus isolates, 88.5% were resistant to methicillin.Conclusion: Staphylococcus, with a high frequency in the NICU, can be an alarm for medical centers. Also, in dead infants, the most observed bacterial infection was Acinetobacter infection, which requires the serious attention of the hospital infection control unit.